Hot–Cold Confusion: Inverse Thermal Sensation When Hot and Cold Stimuli Coexist in a Thermal Localization Task. (June 2021) - Arai, Keisuke; Matsumuro, Miki; Hashiguchi, Satoshi; Shibata, Fumihisa; Kimura, Asako
We focused on the inverse thermal sensation caused by the presence of both hot and cold stimuli, which we named hot–cold confusion . Some researchers have shown that when participants touch a thermal stimulus simultaneously with two opposite thermal stimuli on both sides, the outer temperatures dominate the center temperature; for example, a hot stimulus between two cold stimuli is perceived as cold. However, there has not been sufficient research on the effect of the center stimulus on the outer stimuli. In the current study, we placed a participant's forearm on an alignment where hot and cold stimuli were alternately placed in three locations and found that the participants sometimes selected the inverse thermal sensation of the presented surface not only at the center but also at the outer locations. Namely, opposite thermal stimuli applied at multiple locations affected each other, and the participants sometimes perceived the hot stimulus at the outer location as cold even when the two of three stimuli were hot, and vice versa. In addition, using various alignments of thermal stimuli, we revealed a directional bias of the effect from the cold stimulus and a difference in strength according to its location on the forearm.